Influence and Predictors of Anxiety on Health Status ≥ 5 Years Beyond Breast Cancer Diagnosis in Spain: A Cross-Sectional Study - Francisco Álvarez-Salvago; Clara Pujol-Fuentes; Jose Medina-Luque; Maria Figueroa-Mayordomo; Carmen Boquete-Pumar; Sandra Atienzar-Aroca (Life)
Purpose: To explore the association between anxiety levels and health outcomes in long-term breast cancer survivors (LTBCSs) and to identify predictors of anxiety in this population. Methods: A multicenter cross-sectional study was conducted with 80 LTBCSs, categorized into two groups based on their anxiety levels: low anxiety (≤3.4) and high anxiety (≥3.5). The analysis focused on variables assessed at least five years after diagnosis, including sociodemographic and clinical data, mood, cancer-related fatigue (CRF), pain, self-perceived physical fitness, physical activity (PA), and health-related quality of life (HRQoL). ANOVA, Mann–Whitney U, and chi-square tests were conducted, along with correlation and multiple regression analysis. Effect sizes were calculated using Cohen’s d. Results: Among the participants, 46.25% exhibited higher anxiety levels. This group showed significantly worse mood, self-perceived physical fitness, and HRQoL and elevated CRF and pain (p < 0.05). Regression analysis identified “total CRF” (β = 0.51; p < 0.01) and “cognitive functioning” (β = −0.24; p = 0.02) as significant predictors of higher levels of anxiety (r2 adjusted = 0.470). Conclusions: Anxiety significantly impacts multiple dimensions of health in LTBCSs. Total CRF and cognitive functioning are key predictors of anxiety. These findings have direct clinical implications: routine psychological and physical assessments should be integrated into survivorship care to identify individuals at risk and inform targeted interventions to enhance long-term well-being and HRQoL.